2021
DOI: 10.3390/v13101950
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Injury Caused by Genotype 4 Hepatitis E Virus Infection Based on a BALB/c Mice Model

Abstract: To evaluate whether uterine injury caused by hepatitis E virus (HEV) infection is responsible for adverse pregnancy outcomes. HEV-infected female BALB/c mice were coupled with healthy male BALB/c mice at 0, 7, 14, 21, and 91 dpi to explore the uterine injury caused by HEV infection. Mice were euthanized after 10 days of copulation, and uteruses were collected for HEV RNA and antigen detection and histopathological analysis. Inflammatory responses; apoptosis; and estrogen receptor ɑ (ER-ɑ), endomethal antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…In view of the adverse pregnancy and relatively high mortality of pregnant women caused by HEV, human trophoblast cells (JEG-3) were selected as an in vitro model. In addition, it has been reported that HEV can infect pregnant mice, causing miscarriage and uterine injury in female mice [ 29 ]. Therefore, whether HEV-3 could infect JEG-3 cells and the placenta of pregnant mice was first investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the adverse pregnancy and relatively high mortality of pregnant women caused by HEV, human trophoblast cells (JEG-3) were selected as an in vitro model. In addition, it has been reported that HEV can infect pregnant mice, causing miscarriage and uterine injury in female mice [ 29 ]. Therefore, whether HEV-3 could infect JEG-3 cells and the placenta of pregnant mice was first investigated.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that uterine damage in relation to endometrial thinning enhanced inflammatory response, and increased programmed cell death could be causative factors of pregnancy pathology. Moreover, they demonstrated the recovery of uterine layers and improvement in fertility after the clearance of HEV from female BALB/c mice [ 116 ].…”
Section: Characteristics Of An Ideal Model Recapitulating Hev Infecti...mentioning
confidence: 99%
“…However, it leads to chronic infection in immunocompromised patients, such as organ‐transplanted recipients 2 or patients with human immunodeficiency virus (HIV) infection 3 . Although HEV predominantly replicates in the liver, multiple extrahepatic HEV replication sites, including the brain, 4,5 placenta, 6,7 uterus, 8,9 testes, and epididymis, 10,11 have been identified. HEV RNA first detected in the sperm is associated with infertility 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…HEV replication in the placenta results in severe fibrosis and calcification, which is responsible for adverse pregnancy outcomes 7 . In addition, the replication of HEV in the uterus causes thinning endometrial thickness (EMT), severe inflammatory responses, and aggravated apoptosis also contribute to poor pregnancy 8 . However, the damage to the female genital tract caused by HEV infection is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation